Single molecule studies of a voltage-gated potassium channel - Angué, L (2013)
This thesis aims to study the activation and deactivation mechanism of voltage-gated K+ channels (Kv), through fluorescence and electrical measurements. Transmembrane voltage changes are detected by the voltage sensor (helices S3b-S4) among Kv, a phenomenon which triggers a conformational change to open or close the pore. By attaching a fluorescent tag on helices S3b-S4, voltage sensor movement can be followed by fluorescence and pore opening or closure by electrical recordings. KvAP, a channel from an archaea organism was selected for this task. Channels were expressed, purified and fluorescently labelled before being reconsituted into droplet interface bilayers (DIB). The degree of labelling was determined by photobleaching measurements. Electrical activity and diffusion were recorded at the single molecule level. Further developments of the technique need to be achieved before successfully correlating fluorescence and electrical recordings at the single molecule level. However, both signals could be simultaneously recorded at bulk and single molecule levels, paving the way for future experiments.